2020
DOI: 10.3390/ijms21218406
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Mechanisms of Itch in Psoriasis

Abstract: Itch (or pruritus) was not previously recognized as a serious symptom of psoriasis. However, approximately 60–90% of psoriatic patients with pruritus have stated that it deteriorates their quality of life. Since conventional antipruritic therapies, such as antihistamines, only exert limited effects, the establishment of a treatment option for itch in psoriasis is urgently needed. Although a definitive drug is not currently available, various itch mediators are known to be involved in pruritus in psoriasis. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 163 publications
(272 reference statements)
2
63
0
2
Order By: Relevance
“…The role of inflammation in psoriatic-related itch origin is undoubtedly relevant, as it is confirmed by elevated concentration of a number of inflammatory mediators and by an antipruritic effect of anti-inflammatory drugs. Various immune cells secrete cytokines that directly or indirectly may aggravate or even induce itch by increasing the inflammatory response [ 45 ]. Nakamura et al analyzed differences in cytokine expression in the epidermis between pruritic and non-pruritic psoriatic patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of inflammation in psoriatic-related itch origin is undoubtedly relevant, as it is confirmed by elevated concentration of a number of inflammatory mediators and by an antipruritic effect of anti-inflammatory drugs. Various immune cells secrete cytokines that directly or indirectly may aggravate or even induce itch by increasing the inflammatory response [ 45 ]. Nakamura et al analyzed differences in cytokine expression in the epidermis between pruritic and non-pruritic psoriatic patients.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Madej et al showed that serum concentration of vascular adhesion protein-1 (VAP-1), another adhesion molecule, was significantly higher in the group of psoriatic patients with pruritus vs. those without pruritus [ 50 ]. Prostaglandin E2 (PGE2), endothelin-1 (ET-1) and endothelial leukocyte adhesion protein 1 (ELAM-1) have also been considered to be good candidates as itch mediators in psoriasis but future studies are required to confirm this hypothesis [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the most prevalent symptoms of psoriasis such as scaling, thickening of skin lesion, and redness, itch is not visible [90]. Historically, itch has been used to differentiate AD from psoriasis – the former being characterized pruritic, while the latter has often been considered nonpruritic.…”
Section: Psoriasismentioning
confidence: 99%
“…Psoriasis is the most prevalent, chronic, inflammatory, and multisystem disease with primarily skin and joint manifestations that affects millions of people worldwide with a deleterious impact on their quality of life [89][90][91][92][93]. The term psoriasis, derived from the Greek word "psora," can also be translated as "to itch" [94].…”
Section: Psoriasismentioning
confidence: 99%
“…Approximately 60–90% of patients with psoriasis have pruritus, and it deteriorates their quality of life. Komiya et al reviewed the features of pruritus in psoriasis and discussed the mechanisms by which a variety of itch mediators induce or aggravate itch in psoriasis [ 8 ]. Various types of neuropeptides, substance P, calcitonin gene-related peptide, neuropeptide Y, act on nerves to induce itch.…”
mentioning
confidence: 99%